Pengelolaan Limbah Pertanian dan Rumah Tangga Berbasis Masyarakat di Desa Nglegi Patuk Gunungkidul, Yogyakarta - Surahma Asti Mulasari (Jurnal Pengabdian Pada Masyarakat, 2018)
COMMUNITY-BASED MANAGEMENT OF AGRICULTURAL AND HOUSEHOLD WASTE IN NGLEGI VILLAGE OF PATUK, GUNUNGKIDUL, YOGYAKARTA. This program focusses on particular issues in Nglegi Patuk Gunung Kidul that is the abundance of agricultural waste, the large number of household waste that does not proceed correctly. The purpose of this activity was to increase community participation in processing domestic waste. The training participants were PKK villages from Nglegi Village. This program offered how to proceed the household waste with the 3R (Reuse, Reduce, Recycle) method. This activity conducted through lecture and demonstration on household and agricultural waste processing. The results of this activity were this program can improve the community knowledge and expected can change the community behavior.